Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Bawang Merah Di Desa Balongmacekan, Kecamatan Tarik, Kabupaten Sidoarjo - Ismi Rosyidatul Ummah; Joko Priyono (Nirta Learning Centre, 2024)
The purpose of this study was to analyze the factors that influence the demand for shallots in Balongmacekan Village, Tarik District, Sidoarjo Regency. The type of data used is quantitative data. The analytical method used is multiple linier regression analysis with the help of the SPSS Windows Version 25.0 program. The data sources for this study include primary data obtained from distributing questionnaires to housewife respondents in Balongmacekan Village and secondary data obtained from Balongmacekan Village. In this study, the sampling technique used was to use a simple random sample with a total of 90 respondents. The results showed that the price of shallots (X1) had a negative and significant effect on the demand for shallots and the number of family members (X3) had a positive and significant effect on the demand for shallots, while income (X2) did not have a significant effect on the demand for shallots in Tarik District, Sidoarjo Regency. It is hoped that this information can provide benefits or input to the community in Balongmacekan Village, Tarik District, Sidoarjo Regency to always be wise in making decisions about changes in terms of price in buying shallots which will later be used for consumption.